Lack of induced chemical changes in leaves of susceptible alternate hosts of Cronartium spp. after inoculation by Cronartium pini and C. ribicola - Piispanen, Juha; Bergmann, Ulrich; Karhu, Jouni; Kauppila, Tuomas; Witzell, Johanna; Kaitera, Juha (Springer Nature, 2025)
Phenolic compounds, known for their antioxidant and antifungal properties may be connected to infection processes of Cronartium rusts in alternate host plants. We studied changes in leaf chemistry after Cronartium inoculation on susceptible alternate hosts of C. pini and C. ribicola. Impatiens balsamina and Paeonia lactiflora were inoculated with C. pini, and R. nigrum with C. ribicola in the greenhouse. Leaves of the inoculated plants were harvested 3 and 6 days after inoculation for chemical analysis, which was done using LC–MS (liquid chromatography mass spectrometry). Species-specific differences were found in dominant phenolics ferulic acid, hyperoside, quercitrin, and rutin. Rust inoculation produced limited changes in phenolic concentrations, with significant increases only in p-coumaric acid in I. balsamina and rutin in R. nigrum. Significant post-inoculation decrease was found in several cases. While phenolic fluctuations varied by species and incubation time, there was no significant interaction between inoculation and incubation time, suggesting the absence of induced phenolic accumulation during early infection stages. The results support the hypothesis that susceptible alternate hosts exhibit weak, delayed phenolic defenses, possibly due to rust virulence factors suppressing these responses. Indirectly, they provide support for the defensive role of phenolics in resistant congeneric hosts, emphasizing also the importance of further molecular studies to explore plant defense mechanisms against rust pathogens.
Keywords: alternate hosts; leaf compounds; rust resistance; Scots pine blister rust; white-pine blister rust